To study the patient satisfication at a tertiary care hospital in Malwa region of Punjab - Goshist, Rahul; Monga, Shamim; Devgan, Shalini; Singh, Baltej; Gupta, Sanjay (International Journal Of Community Medicine And Public Health, 2017)
Background: Many factors including poor systems and stress of the caregivers effects the quality along with satisfaction of patients. Patient satisfaction denotes the extent to which general health care needs of the clients are met to their requirements. Aim of the study to study the level of patient satisfaction. Methods: The structured questionnaire was administered to patients from in-patient areas. Illiterate patients were interviewed personally. The hospital had bed strength of 890 and the patients were followed in different departments till the completion of sample size. Results: More than half of the patients i.e. 58.6% and 54.7% responded that the stretcher availability and behavior of paramedical staff in emergency as poormore than half of the patients i.e. 58.6% and 54.7% responded that the stretcher availability and behavior of paramedical staff in emergency as poor, more than half of the patients i.e. 58.6% and 54.7% responded that the stretcher availability and behavior of paramedical staff in emergency as poor. Conclusions: Most patients rated the services of the hospital as excellent or good but a portion of patients were found to be unsatisfied in some areas i.e. cleanliness of toilets, wards, canteen and behaviors of paramedical staff.